Araceae Of The Crocker Range National Park Sabah: A Preliminary Survey, Checklist And Generic Key. - Boyce, Peter C.; Sulaiman, Baharuddin; Lintong, Jain (ASEAN Academic Press London, 2001)
A preliminary survey tabulated and referenced checklist and generic key to the Araceae of the Crocker Range Park is presented based on fie fieldwork undertaken during the Crocker XPDC'99 supplemented with surveys of specimens in major Asian and European herbaria. A total of 16 genera comprising 73 species of which 70 are indigenous to Sabah are recorded.